Analysis of Kinetic Parameters and Effect of Pt Loading on Cell Performance of PEFC Electrodes Prepared by Inkjet Printing. (14th September 2015) - Shukla, Shantanu; Domican, Kailyn; Secanell, Marc
Abstract : The changes to cell performance, Tafel slope and reaction order with varying Pt loadings and catalyst layer (CL) thickness of 0.014 to 0.1mg/cm 2 and 1 μm to 5.5 μm respectively are studied by using a varietyof oxygen partial pressures for the case of thin, low-loaded inkjet printed electrodes. For 20% Pt/C catalyst, a steep increase in performance was observed as the Pt loading increased to 0.079 mg/cm 2, corresponding to a CL thickness of around 4.4 μm. At higher Pt loadings, the improvement in the cell performance was substantially reduced. Higher cell performance for the inkjet printed CCMs could be obtained by altering the operating conditions (e.g., operating at a higher back-pressure) rather than increasing the Pt loading. Active area of the electrodes decreased from 57 to 41 m 2 /g as the Pt loading increased from 0.026 to 0.1 mg/cm 2 . Below the transition voltage of 0.8 ViRFree, Tafel slope was found to be a function ofthe Pt loading and oxygen partial pressure (PO2 ). The kinetic reaction order (γ) increased with increasing overpotential for all the Pt loading cases.